Faktor Risiko Komplikasi Kronik pada Pasien DM Tipe 2 di RSUP Dr. Wahidin Sudirohusodo Kota Makassar - Wahyuni, Andi Nur Afifah Wahyuni; Andi Selvi Yusnitasari; Indra Dwinata; Rizky Chaeraty Syam (LPPM Hang Tuah Pekanbaru, 2025)
Introduction: DM prevalence keeps rising, with 90-95% of cases being DMT2, which, if not treated properly, will cause various complications. Around 30-50% of DMT2 sufferers experience complications, with the proportion at Dr. Wahidin Sudirohusodo Hospital reaching 49.7%. High complications stem from uncontrolled factors, making optimal management key to prevention. Aim: Analyze risk factors for chronic complications in DMT2 patients at Dr. Wahidin Sudirohusodo Hospital. Method: Observational analytic with case control design. The population included DMT2 patients at Dr. Wahidin Sudirohusodo Hospital, with 158 samples (79 cases and 79 controls) selected using purposive sampling. Data were collected through interviews and medical records, and then analysed univariately, bivariately, and multivariately. Results: Multivariate statistical analysis with multiple logistic regression showed significant results for the variables age (3.62), duration of DM (4.83), medication compliance (3.26), blood sugar control (3.63), and stress (6.82). Conclusion: Age, duration of DM, medication compliance, blood sugar control, and stress are significant risk factors for complications, with stress as the most influential factor. Therefore, DMT2 patients need to manage stress, routinely control blood sugar, and comply with treatment to prevent more serious complications.